Policy bias and agriculture: partial and general equilibrium measures - Bautista, Romeo M.; Robinson, Sherman; Tarp, Finn; Wobst, Peter (International Food Policy Research Institute, 1998)
The paper examines the impact of industrial protection, agricultural export taxes, and overvaluation of the exchange rate on the balance between the agricultural and non-agricultural sectors. A variety of agricultural terms-of-trade indices are constructed to measure the policy bias against agriculture in a general equilibrium framework that incorporates traded and non-traded goods. These general equilibrium measures are compared to earlier work in a partial equilibrium framework assuming perfect substitutability between domestic and traded goods. Starting from a stylized computable general equilibrium (CGE) model of Tanzania, we simulate a 25 percent tariff on non-agriculture and a 25 percent export tax on agriculture. We also consider the impact of changes in the equilibrium exchange rate. The results indicate that the partial equilibrium measures miss much of the action operating through indirect product and factor market linkages, while overstating the strength of the linkages between changes in the exchange rate and prices of traded goods on the agricultural terms of trade.